PENGARUH PERCEIVED USEFULNESS DAN PERCEIVED EASE TO USE PADA NIAT MENGGUNAAN APLIKASI TIKTOK DIMASA PANDEMI (STUDI PADA GENARI Z DI BALI) - Indah Kumala Sari; Anak Agung Elik Astari; Ni Luh Indiani (Bajang Institute, 2022)
This study aims to determine the effect of perceived usefulness, perceived ease of use on intentions to use the TikTok application. This study uses a quantitative approach with data collection methods through online questionnaires and is determined using a non-probability purposive sampling method. Data was obtained by distributing online questionnaires to 65 Generation Z respondents who had never used the TikTok application. The results of this study indicate that perceived usefulness and perceived ease of use affect the intention to use the TikTok application either partially or simultaneously according to the results of statistical data processing which found that all hypotheses were accepted. used as a reference for further research. The main theory in this study uses the Technology Acceptance Model (TAM) which is used to explain the relationship between perceived benefits, perceived ease of use and intention to use, and it is found that perceived usefulness, perceived ease of use, are still strong predictors in increasing intention to use the TikTok application. in generation Z. The results of the R-Square score of 0.623 which indicates that the intention to use the TikTok application in generation Z is influenced by 62% influenced by perceived usefulness, perceived ease of use and the rest is influenced by other things that are not explained in this study. This study contributes to the literature on the topic of social media use by considering perceived usefulness and ease of influencing intentions to use TikTok